Efficacy of L-carnitine combined with erythropoietin in the treatment of hemodialysis-induced renal anemia - ZHANG Yong; HOU Juan (Linchuang shenzangbing zazhi)
Objective To investigate the therapeutic effect of levocarnitine and erythropoietin(EPO)in hemodialysis patients with renal anemia.Methods Eighty patients with hemodialysis-induced renal anemia admitted from January 2015 to December 2016 were randomly divided into two groups by the random number table(n=40 in each group).The patients in the control group were treated with EPO.The patients in the treatment group were treated with levocarnitine on the basis of the control group.The hemoglobin,hematocrit value,serum ferritin,serum albumin transferrin saturation,the overall therapeutic effect,left ventricular remodeling and adverse reactions were compared between two groups.Results After treatment,the hemoglobin,hematocrit value,serum ferritin and serum albumin transferrin saturation in the treatment group were(106.52±9.42)g/L,(28.17±2.55)%,(268.22±40.35)μg/L,(31.59±5.60)%,respectively,which were significantly higher than those in the control group [(95.72±8.29)g/L,(25.35±2.13)%,(220.07±41.94)μg/L,(26.48±4.91)%].parathyroid hormone,P3-,anteroposterior diameter of left atrium,left ventrianfar systolic diameter and left ventrianfar systolic diameter in the treatment group were(59.80±11.34)mmol/L,(1.39±0.37)mmol/L,(31.32±0.87)mmol/L,(32.17±1.20)mm,and(54.85±1.41)mm respectively,which were significantly lower than those in the control group [(84.60±17.56)mmol/L,(1.77±0.45)mmol/L,(33.92±1.13)mmol/L,(33.89±1.06)mm,(58.42±1.57)mm](P<0.01).The significant efficiency rate in the treatment group was significantly higher than that in the control group(P<0.05).There was no significant difference in the incidence of adverse reactions between the two groups(P>0.05).Conclusions The application of levocarnitine and EPO in patients with hemodialysis-induced renal anemia has significant curative effect,which can significantly improve the anemia indicators and promote ventricular remodeling,thereby enhancing the therapeutic effect,while being highly safe and not prone to adverse reactions.